Sociological Aspects and Local Specificity in the Classical Ketoprak Script of Surakarta Style - Bagus Wahyu Setyawan; Kundharu Saddhono; Ani Rakhmawati (Journal of Language and Literature, 2017)
Javanese literary works are reflections of the scriptwriters real world. Ketoprak script is one of the literary works of the traditional Javanese drama genre. There are several kinds of ketoprak scripts in Java and each region has different aspects. Each ketoprak text can reflect the social condition of its native area when analyzed by sociological literary-approach. Sociology of literature is a study that connects literature with its social reality. Classical ketoprak script of Surakarta style viewed from the perspective of sociological literature is a reflection of the socio-cultural life of the community in Surakarta. It is seen from a socio-historical perspective, socio-cultural, and linguistic aspects used in the classical ketoprak script of Surakarta style. These three aspects make the classical ketoprak script of Surakarta style has a local specificity and characteristics that distinguish it from other Javanese literature.Keywords: sociological aspect, local specificity, Javanese literature, classical ketoprak script